2010
DOI: 10.3354/ab00225
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shift in the foraging niche of Atlantic puffins Fratercula arctica revealed by stable isotope (δ15N and δ13C) analyses

Abstract: We measured tissue stable nitrogen (δ 15 N) and carbon (δ 13 C) values to investigate the extent of seasonal and age-related variation in the foraging ecology of Atlantic puffins. For adults, there was considerable seasonal variation in the foraging niche. A generalized, lower trophic level (TL) diet during the winter moult was replaced by a highly specialized, higher TL diet during summer when birds were rearing chicks. The seasonal δ 15 N enrichment of 2.36 ‰ is consistent with an increase of 0.65 TL. Output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…to krill as inferred by Hedd et al . (). Little is known about the winter distribution or diet of the Gulf of Maine Puffin population, but stable‐isotope (δ 15 N, δ 13 C) analysis of MSI chick and winter‐grown adult Puffin feathers shows neither the seasonal difference in diet described by Hedd et al .…”
Section: Discussionmentioning
confidence: 97%
“…to krill as inferred by Hedd et al . (). Little is known about the winter distribution or diet of the Gulf of Maine Puffin population, but stable‐isotope (δ 15 N, δ 13 C) analysis of MSI chick and winter‐grown adult Puffin feathers shows neither the seasonal difference in diet described by Hedd et al .…”
Section: Discussionmentioning
confidence: 97%
“…The larger isotopic niche for both islands during the non-breeding season can be explained by the fact that birds, when not constrained by the duties of incubation and chick-rearing, adopt a wide range foraging strategy, often reflect in a larger isotopic niche width (Ceia et al, 2014;Hedd et al, 2010;Kowalczyl et al, 2013;, this study). There were marked differences in the occurrence of cephalopods in the diet between years, irrespective of island, likely revealing strong differences in the foraging ecology of Macaronesian shearwaters between the breeding seasons of 2011 and 2012.…”
Section: Annual Differences In Isotopic Nichementioning
confidence: 95%
“…3) Given the fact that carbon is enriched in coastal in relation to offshore predators (Hobson et al, 1994;Cherel et al, 2005), the presumably nearshore-foraging birds from Selvagem Grande are expected to have higher δ 13 C values than the more offshore-foraging birds from Porto Santo (Paiva et al, 2010a). 4) By foraging on both pelagic (around Selvagem Grande) and more coastal waters (Canary current system), birds from Selvagem Grande should show a broad isotopic niche (Bolnick et al, 2007;Hedd et al, 2010), but with a higher individual consistency in that niche (i.e. a greater variation among individuals than within individuals because some individuals may specialize to feed predominantly in coastal waters and other individuals in pelagic waters; Bearhop et al, 2006;Ceia et al, 2012;Votier et al, 2010).…”
mentioning
confidence: 99%
“…Thus, even if herring is important, this strongly suggests that other prey played a larger role in determining the puffin egg size. Recent stable-isotope studies (Davies et al 2009, Hedd et al 2010 have suggested that Atlantic puffins and their sibling species tufted puffins Fratercula cirrhata prey on zooplankton in winter and the early breeding season. Furthermore, Sorensen et al (2009) showed that pre-breeding female Cassin's auklets Ptychoramphus aleuticus that fed on energetically superior copepods laid earlier and larger eggs than those that fed on poorer juvenile rockfish Sebastes spp.…”
Section: Environmental Factorsmentioning
confidence: 99%